2023
DOI: 10.1002/wene.473
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on how ionic liquids enhance the pyrolysis of cellulose, lignin, and lignocellulose toward a circular economy

Abstract: The sustainable use of plant biomass (PB) to produce new valuable compounds helps alleviate the world's excessive reliance on fossil fuels. Among the different processes available, pyrolysis has drawn significant attention for its efficiency in converting PB (including lignin, hemicellulose, and cellulose) into solid, liquid, and gas products by thermal degradation. Moreover, the participation of ionic liquids (ILs) in the pyrolysis process can further facilitate this process, improve the quality of pyrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 235 publications
(264 reference statements)
0
8
0
Order By: Relevance
“…The broad peak observed at 3400–3900 cm −1 is mainly dedicated to –OH stretching. [ 30,33,35 ] The intensity of this peak is higher in char obtained from pyrolysis without catalyst. This functional group is related to alcohols and its high intensity indicates the high amount of oxygen in it.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The broad peak observed at 3400–3900 cm −1 is mainly dedicated to –OH stretching. [ 30,33,35 ] The intensity of this peak is higher in char obtained from pyrolysis without catalyst. This functional group is related to alcohols and its high intensity indicates the high amount of oxygen in it.…”
Section: Resultsmentioning
confidence: 98%
“…Aromatic compounds originated from the thermal degradation of lignin in the poplar wood structure and aromatic chain in waste tyre. [ 33 ] Additionally, acids and alcohols were mainly derived from the cracking of cellulose and hemicellulose in the wood structure, as well as the cracking of functional group chains in the waste tyre. The comparison of the results showed that aromatics were more intense than other groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-carbon recycling is the practice of recycling and reusing refuse to lessen resource loss and environmental damage. Circular economies (Eqbalpour et al, 2023), sustainable resource management, and refuse recycling (Porshnov, 2022) are just a few examples of low-carbon recycling methods that are now commonly used. For trash management to be more effective and viable, low-carbon recycling needs to put more emphasis on resource integration and sharing.…”
Section: Introductionmentioning
confidence: 99%